Documents of the Christian church - Bettenson, Henry, 1908-1979.; Maunder, Chris (Oxford ; New York : Oxford University Press, 2011)
"This selection of writings vividly captures the most important moments in the history of Christianity, providing insights into 2000 years of Christian theological and political debate. The anthology was first published in 1943, and has since become established as a classic reference work. While retaining the original material selected by Henry Bettenson, Chris Maunder added in 1952 a substantial section of more recent writings for the third edition. These illustrate the Second Vatican Council; the theologies of liberation; Church and State from Thatcher's Britain to Communist Eastern Europe; Black, feminist, and ecological theology; ecumenism; and inter-faith dialogue. The emphasis on moral debate in the contemporary churches is reflected in sections discussing questions about homosexuality, divorce, AIDS and in-vitro fertilization. This expanded fourth edition brings the anthology up to date with a new section looking at major issues facing the twenty-first century churches. This includes extracts exploring the churches' responses to questions of social justice, international politics, trade and debt, environmental change and technological development, including the Internet. The new edition also examines the global growth of Christianity, the progress of Christian unity, mission in multi-faith societies, disability, migration, domestic violence and addiction"--Page 4 of cover.
The church and the world -- Creeds -- The earliest testimony to the Gospels -- The person and work of Christ -- The problem of the relation of the divinity and the humanity in Christ -- Pelagianism : human nature, sin, and grace -- The church, the ministry, and the sacraments -- The authority of the Holy See -- Doctrine and development : the Vincentian canon -- Christian inscriptions -- From Chalcedon to the breach between East and West -- The empire and the papacy -- Monasticism and the friars -- The church and heresy -- The conciliar movement -- Scholasticism -- The church in England until the Reformation -- The Reformation on the continent -- The Reformation in England -- The Roman Catholic Church from the Counter-Reformation to the Second Vatican Council -- The British churches in the seventeenth century -- The British churches in the eighteenth and nineteenth centuries -- The Roman Catholic Church at the Second Vatican Council -- The twentieth-century world churches : justice, peace, and the environment -- The twentieth-century world churches and inter-faith dialogue -- The twentieth-century churches and Christian unity -- The twentieth-century churches : sexuality and procreation -- The churches and twenty-first-century issues.
Includes bibliographical references (pages 511-514) and index.
Keywords: Church history -- Sources